Neurological Abnormalities in Recent-Onset Schizophrenia and Asperger-Syndrome - Hirjak, Dusan; Wolf, Robert Christian; Koch, Sabine C.; Mehl, Laura; Kelbel, Janna K.; Kubera, Katharina Maria; Traeger, Tanja; Fuchs, Thomas; Thomann, Philipp Arthur (Frontiers in Psychiatry, 2014)
Background: Neurological abnormalities including a variety of subtle deficits such as discrete impairments in sensory integration, motor coordination, and sequencing of complex motor acts are frequently found in patients with schizophrenia and commonly referred to as neurological soft signs (NSS). Asperger-Syndrome (AS) is characterized by sensory-motor difficulties as well. However, the question whether the two disorders share a common or a disease-specific pattern of NSS remains unresolved. Method: A total of 78 age- and education-matched participants (26 patients with recent-onset schizophrenia, 26 individuals with AS, and 26 healthy controls) were recruited for the study. Analyses of covariance (ANCOVAs), with age, years of education and medication included as covariates, were used to examine group differences on total NSS and the five subscale scores. Discriminant analyses were employed to identify the NSS subscales that maximally discriminate between the three groups. Results: Significant differences among the three groups were found in NSS total score and on the five NSS subscales. The two clinical groups differed significantly in the NSS subscale „motor coordination”. The correct discriminant rate between patients with schizophrenia and individuals with AS was 61.5%. The correct discriminant rate was 92.3% between individuals with AS and healthy controls, and 80.8% between schizophrenia patients and healthy controls, respectively. Conclusions: Our findings provide new evidence for the presence of NSS in AS and lend further support to previously reported difficulties in movement control in this disorder. According to the present results, schizophrenia and AS seem to be characterized by a different pattern of NSS.